Complications related to entry techniques for laparoscopy in 159 dogs and cats. Issue 5 (14th May 2019) - Anderson, Scott J.; Fransson, Boel A.
Abstract: Objective: To report the frequency and risk factors of complications related to 3 entry techniques for laparoscopy in small animals. Study design: Single‐institution retrospective case series. Animals: 159 client‐owned dogs and cats. Methods: Medical records were reviewed for dogs and cats undergoing laparoscopic surgery with carbon dioxide (CO2 ) insufflation between 2006 and 2018. Data including entry site, entry technique, signalment, body conformation, complications, and operating surgeon/resident were analyzed by univariate regression analysis. Factors with P  < .25 were included in multivariate regression analysis. Results: Complications occurred in 33 of 159 (21%) surgeries and were considered minor (CO2 leaks, omental insufflation, repeated entry) in 30 of 33 (91%) cases. The Ternamian visual entry, modified Hasson, and Veress needle entry techniques were associated with complications in 7 (9%), 17 (26%), and 9 (60%) surgeries, respectively. Major complications occurred in 3 of 159 (2%) surgeries, in which entry‐related hemorrhage prompted conversion to an open technique (2 [13%] entries with Veress needle) and 1 [1%] with the Ternamian visual). Entry location and entry technique remained significant in the final multivariate model. Complications were 11.7 times more likely after a paramedian entry than after a midline entry; the odds ratio of complications were 5 and 28 times higher after modified Hasson and Veress needle entries, respectively, than after Ternamian visual entry. Conclusion: In this study, a Ternamian visual entry technique and midline entry site appeared associated with fewer complications than 2 other techniques. Clinical significance: The findings in this study are preliminary, and superiority of any entry technique must be reevaluated in a prospective randomized controlled study.